Atomic-scale understanding of high thermal stability of the Mo/CoFeB/MgO spin injector for spin-injection in remanence. Issue 21 (23rd May 2018) - Tao, Bingshan; Barate, Philippe; Devaux, Xavier; Renucci, Pierre; Frougier, Julien; Djeffal, Abdelhak; Liang, Shiheng; Xu, Bo; Hehn, Michel; Jaffrès, Henri; George, Jean-Marie; Marie, Xavier; et al.
Abstract : Remanent spin injection into GaAs based LEDs with a thermally stable Mo/CoFeB/MgO spin injector. Abstract : Remanent spin injection into a spin light emitting diode (spin-LED) at zero magnetic field is a prerequisite for future application of spin optoelectronics. Here, we demonstrate the remanent spin injection into GaAs based LEDs with a thermally stable Mo/CoFeB/MgO spin injector. A systematic study of magnetic properties, polarization-resolved electroluminescence (EL) and atomic-scale interfacial structures has been performed in comparison with the Ta/CoFeB/MgO spin injector. The perpendicular magnetic anisotropy (PMA) of the Mo/CoFeB/MgO injector shows more advanced thermal stability than that of the Ta/CoFeB/MgO injector and robust PMA can be maintained up to 400 °C annealing. The remanent circular polarization ( P C ) of EL from the Mo capped spin-LED reaches a maximum value of 10% after 300 °C annealing, and even remains at 4% after 400 °C annealing. In contrast, the Ta capped spin-LED almost completely loses the remanent P C under 400 °C annealing. Combined advanced electron microscopy and spectroscopy studies reveal that a large amount of Ta diffuses into the MgO tunneling barrier through the CoFeB layer after 400 °C annealing. However, the diffusion of Mo into CoFeB is limited and never reaches the MgO barrier. These findings afford a comprehensive perspective to use the highly thermally stable Mo/CoFeB/MgO spin injector for efficient electrical spin injection in remanence.